Magna Carta and the idea of liberty (Robert E. Krieger Publishing, 1982)
This collection presents contemporary views and seventeenth-century arguments, as well as modern attitudes toward the Charter. Comparisons with other similar documents of liberty and extracts from and commentaries on some of these are also presented